2016
DOI: 10.1111/ajt.13693
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Transplantation: Skin as a Sentinel Marker for Rejection

Abstract: These authors contributed equally.Abdominal wall transplantation (AWTX) has revolutionized difficult abdominal closure after intestinal transplantation (ITX). More important, the skin of the transplanted abdominal wall (AW) may serve as an immunological tool for differential diagnosis of bowel dysfunction after transplant. Between August 2008 and October 2014, 29 small bowel transplantations were performed in 28 patients (16 male, 12 female; aged 41 AE 13 years). Two groups were identified: the solid organ tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 36 publications
1
49
2
1
Order By: Relevance
“…The Oxford group describe their experience with using the abdominal wall transplant skin as a sentinel marker for rejection in 13 adult patients transplanted using the microvascular technique, including five abdominal wall transplants with temporary remote vascularization in the forearm because of a predicted long cold ischaemia time of the AWT . This group had six episodes of rejection and two episodes of graft versus host disease (GVHD).…”
Section: Discussionmentioning
confidence: 99%
“…The Oxford group describe their experience with using the abdominal wall transplant skin as a sentinel marker for rejection in 13 adult patients transplanted using the microvascular technique, including five abdominal wall transplants with temporary remote vascularization in the forearm because of a predicted long cold ischaemia time of the AWT . This group had six episodes of rejection and two episodes of graft versus host disease (GVHD).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of early signs of acute rejection being visible on the skin component of a VCA is the focus of on-going research. The role of the AWT as a sentinel skin graft leading to early detection and treatment of rejection for both VCA and underlying ISB/MVT has been demonstrated [87][88][89]. This may be translated to reduced morbidity by avoiding over immunosuppression.…”
Section: Basic Science In Vcamentioning
confidence: 99%
“…The authors concluded that simultaneous AWA and VOA offers four advantages. (a) It is possible to perform a comfortable closure of the AW; (b) the skin of the AW may be used as an early marker of intestinal rejection; (c) it can help to clarify GVHD and (d) it can be useful for differential diagnosis between intestinal inflammation and rejection 34,35 .…”
Section: Awa In Clinical Practicementioning
confidence: 99%
“…The immunosuppressive regimen in AWA is similar to that used in other VCA or organ transplantation procedures. Induction immunosuppression usually starts with alemtuzumab or daclizumab 8,21,24,30,34 . Maintenance immunosuppression is usually a combination of tacrolimus, mycophenolate mofetyl and prednisone.…”
Section: Immunosuppressive Therapy In Clinical Awamentioning
confidence: 99%
See 1 more Smart Citation